Phase analysis of seeded and doped PbMg1/3Nb2/3O3 prepared by organic solution of citrates - Carvalho, J. C. [UNESP]; Paiva-Santos, C. O. [UNESP]; Zaghete, M. A. [UNESP]; Oliveira, C. F. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Springer Nature, 1996)
PbMg1/3Nb2/3O3 (PMN) prepared by organic solution of citrates was analyzed by the Rietveld method to determine the influence of seeds and dopants on the perovskite and pyrochlore phase formation. It was observed that pyrochlore phase formation increases with an increase in calcination time when no additives are included during the preparation. It was also observed that a greater amount of perovskite phase appeared in doped or seeded samples. The fraction of perovskite phase increased from 88 mol % in pure sample to ∼95 mol % in doped and seeded samples calcined at 800°C for 1 h. It is clear that the addition of dopants or seeds during PMN preparation can enhance the formation of perovskite phase.
Keywords: Barium titanate; Calcination; Composition effects; Doping (additives); Nucleation; Organic compounds; Perovskite; Phase transitions; Citrates; Lead magnesium niobate; Mole fraction; Pyrochlore; Rietveld method; Lead compounds